Seasonality drives the survival landscape of a recovering forest carnivore in a changing world. Issue 1979 (27th July 2022) - Smith, Matthew M.; Erb, John D.; Pauli, Jonathan N.
Abstract : Ecological heterogeneity promotes species persistence and diversity. Environmental change has, however, eroded patterns of heterogeneity globally, stifling species recovery. To test the effects of seasonal heterogeneity on a reintroduced carnivore, American martens ( Martes americana ), we compared metrics of local and season-specific heterogeneity to traditional forest metrics on the survival of 242 individuals across 8 years and predicted a survival landscape for 13 reintroduction sites. We found that heterogeneity—created by forest structure in the growing season and snow in the winter—improved survival and outperformed traditional forest metrics. Spatial variation in heterogeneity created a distinct survival landscape, but seasonal change in heterogeneity generated temporal discordance. All translocation sites possessed high forest heterogeneity but there were greater differences in winter heterogeneity; recovery sites with the poorest snow conditions had the lowest viability. Our work links heterogeneity across seasons to fitness and suggests that management strategies that increase seasonal aspects of heterogeneity may help to recover other sensitive species to continuing environmental change.